تأثير حليب الإبل في بعض التغيرات النسجية لخصى وطحال ذكور الجرذان المختبرية المجرعة Fasciola gigantica براشح أكباد الأبقار المصابة بطفيلي المتورقة الكبدية العملا: Effect of camel’s milk on some histological changes of testis and spleen of male rats treated with cow’s livers infected by Fasciola gigantica - الفرطوسي خالد كاطع (University of Thi-Qar Journal of Science, 2014)
f male rats that treated with cow’s livers infected with Fasciola gigantica . The first part have been treated with temperature (100) centigrade while the second did not treat to heating . The treatment of male rats with livers treated and non treated by heat caused histopathological symptoms in testis tissue performed haemorrhage, necrosis in spermatogenic cells , splitting among seminal tubules , sperm modicums , congestion with hyper pigmentation . Similarly, the spleen showed histological changes involved degenerative in the cells of spleen, necrosis in some lymphatic tissues , congestion of blood vessels , red pulp fibrosis and hyperpigmentation . From other hand, the treatment with camel’s milk was improved in histopathological changes. While, the severity of histopathologicalchanges was decreasing that caused by using of sweating of livers infected, the treatment by camel’s milk was highly effective in the improvement the changes and repair the histological damages .